Malay Version of Nijmegen Cochlear Implant Questionnaire and Quality of Life of Patients with Post-lingual Deafness - Mark PAUL; Asma ABDULLAH; Noor Dina HASHIM; Nur Fadhilah Megat ISMAIL; Shamsul Azhar SHAH (Medeniyet Medical Journal)
Objective: The Nijmegen Cochlear Implant questionnaire (NCIQ) was used to gauge the quality of life (QOL) improvement among cochlear implant (CI) users who suffered from post-lingual deafness. This study aimed to determine the consistency and reliability of the Malay version of the Nijmegen Cochlear Implant questionnaire (NCIQ-M) and to report the QOL of patients using NCIQ-M. Methods: This study has two phases: Phase I involves the translation of the NCIQ from English to Malay, followed by internal consistency and test-retest reliability assessment of the final version of NCIQ-M. Phase II involves QOL assessment of post-lingual deafness using NCIQ-M. Results: Twenty CI users and 20 non-CI users answered the NCIQ-M. Test-retest reliability analysis of the NCIQ-M was performed using an intraclass correlation coefficient, achieving scores of more than 0.85. Internal consistency was analysed with Cronbach α of more than 0.70 in all subdomains. Scores between the two groups of subjects were analyzed using an independent sample t-test. Good internal consistency, intraclass correlation, and test-retest reliability were obtained. Scores in all six subdomains of the NCIQ-M are significantly higher in the CI user group than in the non-CI user group. Conclusions: The NCIQ-M is a consistent and reliable subjective questionnaire to determine the QOL of CI users concerning physical, psychological, and social functioning.